"Her World Gets Smaller and Smaller With Nothing To Look Forward To" Dimensions of Social Inclusion and Exclusion Among Rural Dementia Care Networks - Dorothy Forbes; Catherine Ward-Griffin; Marita Kloseck; Marissa Mendelsohn; Oona St-Amant; Ryan DeForge; Kristine Clark (Rural Nurse Organization; Binghamton University, 2011)
The purpose of this research was to critique the nature of rural dementia care from the perspectives of persons with dementia, their family caregivers and home care providers through a social inclusion/exclusion lens. A critical gerontology approach within a human rights framework (Townsend, 2006) was used. Three rural dementia care networks were included consisting of persons with dementia (n=3), spouse caregivers (n=3), adult children (n=9), grandchildren (n=2) and home care providers (n=3). Thematic analysis (Lubrosky, 1994) revealed three overarching inclusion/exclusion themes. Members of the dementia care network were being denied and afforded opportunities with respect to: (i) experiencing quality relationships among network members; (ii)  having a voice in dementia care decisions; and (iii)  participating in care, social, and work activities. This study contributes evidence that challenges the myth of the idyllic nature of rural places. Findings revealed the diversity of lived experiences within dementia care network members who described both positive (e.g., close community ties, life-long work opportunities) and negative (e.g., stigma of dementia, dangers of rural setting) aspects of the link between living in a rural setting and living with dementia.